Labor Supply Responses to New Rural Social Pension Insurance in China: A Regression Discontinuity Approach - Zeyuan Chen; Tommy Bengtsson; Jonas Helgertz (Institute for the Study of Labor (IZA), 2015)
Transitioning into retirement is an under-researched phenomenon in developing countries. Largely, this is linked to a predominance of contexts where – in particular – the rural population remains outside the coverage of any formal pension system. In 2008, China introduced the New Rural Social Pension (NRSP), a program which by now covers the majority of the Chinese rural elderly. This paper examines the effects of the NRSP on the labor supply of the elderly in rural China. As pension benefit eligibility at the time of its implementation is conditional on age, a regression discontinuity design is applied to investigate the casual effect of the receipt of pension benefits on labor supply. Furthermore, as the NRSP is neither means-tested nor conditions on retirement, it induces a pure income effect on employment. Using data from the China Health and Retirement Longitudinal Study, a nationally representative data set, we find that the receipt of pension benefits increases the probability of retirement among the rural elderly by around 15%.
Keywords: H55; J26; 330; China; New Rural Social Pension; labor supply; regression discontinuity; retirement